The Effect of Collaborative Murder Learning Model on Cognitive Ability and Learning Motivation - Jujun Ratnasari (Jurnal Report of Biological Education, 2020)
Research with this quasi-experimental method aims to determine the influence of collaborative learning models of Mood, Understand, Recall, Detect, Elaborate, and Review (MURDER) on the cognitive abilities and motivational learning of learners. The instrument used to measure the cognitive abilities in the form of written tests refers to the Bloom's taxonomy, while the instrument for measuring learning motivation are motivation questionnaires. Learning cognitive ability data in the form of increase in Pretest and Posttest i.e. the normalization Gain (N-Gain) tested statistically using Wilcoxon test. Wilcoxon test results at a significance level α = 0.05 with 95% confidence level indicates calculated W of 0, while the table W (0.05) (30) amounted to 137. It can be concluded that Ho is rejected meaning that the cognitive abilities in the experiment class and the control class differ significantly. Analysis of learning motivation data was taken from a questionnaire with a Likert scale 1-4. The results of the t test calculation at the significance level α = 0.05 95% confidence level showed calculated t of 0.75, and table t (0.975) (59) of 2,001. Because the t 0.975 (59) < t < t 0.975 (59), it can be concluded that Ho is accepted meaning there is no significant difference in students' learning motivation in the experimental class and the control class. In this study the MURDER collaborative learning model has an effect on cognitive ability, but does not affect learning motivation of students.